A titanium-based photo-Fenton bifunctional catalyst of mp-MXene/TiO2−x nanodots for dramatic enhancement of catalytic efficiency in advanced oxidation processes. Issue 82 (28th September 2018) - Cheng, Xiaomei; Zu, Lianhai; Jiang, Yue; Shi, Donglu; Cai, Xiaoming; Ni, Yonghong; Lin, Sijie; Qin, Yao
Abstract : A pseudo-Fenton reaction works synergistically with photocatalysis to greatly accelerate the oxidative degradation rate. Abstract : mp-MXene/TiO2− x nanodots (NDs) structurally composed of microporous MXene monolayers embedded with Ti 3+ -doped TiO2 nanodots were developed for the first time. The drastically enhanced catalytic efficiency (as much as 13 times higher than that of P25) in degrading dye molecules over mp-MXene/TiO2− x NDs is due to a synergistic effect of the pseudo-Fenton reaction and photocatalysis.